Spin-size effects in stochastic resonance in uniaxial superparamagnets - COFFEY, WILLIAM THOMAS (American Physical Society, 2010)
The relaxation dynamics of a uniaxial paramagnet of arbitrary spin value S, interacting with a thermal bath, are treated using the spin-boson model for a particular spin Hamiltonian consisting of the simplest uniaxial potential in the high temperature, Ohmic damping, and weak spin-bath coupling limits. The signal-to-noise ratio of the magnetic moment fluctuations in the stochastic resonance of such a paramagnet displays a pronounced dependence on S for values of S 20. The dependence arises from the quantum spin dynamics which differs markedly from the magnetization dynamics of classical superparamagnets with S 103?105.
PUBLISHED
Keywords: Physics; superparamagnets